2018
DOI: 10.1111/jbi.13427
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Muller's termite frog suggests the vicariant role of the Central Brazilian Plateau

Abstract: Aim To test three different scenarios to account for the geographic distribution of genetic variation in Dermatonotus muelleri, a fossorial frog endemic of the South American diagonal of open formations (DOF) formed by Chaco, Cerrado, and Caatinga biomes: (a) The pan‐DOF hypothesis, where these biomes behave as a single biogeographical unit and DOF species lack population structure; (b) the southwest‐northeast (SW‐NE) hypothesis, where structured populations along the DOF have either asymmetric or unidirection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 52 publications
2
21
2
Order By: Relevance
“…The geographic break separating these two populations falls in an area of high elevation, which may have isolated the populations. Also, Pleistocene climatic cycles are expected to have influenced the demographic history of at least the Northeast population (Gehara et al, 2017;Oliveira et al, 2018). Oliveira et al (2018) found support for a model of diversification without migration and expansion only for the Northeastern population.…”
Section: Application With Uce Data -Testing Diversification Hypothesementioning
confidence: 89%
See 2 more Smart Citations
“…The geographic break separating these two populations falls in an area of high elevation, which may have isolated the populations. Also, Pleistocene climatic cycles are expected to have influenced the demographic history of at least the Northeast population (Gehara et al, 2017;Oliveira et al, 2018). Oliveira et al (2018) found support for a model of diversification without migration and expansion only for the Northeastern population.…”
Section: Application With Uce Data -Testing Diversification Hypothesementioning
confidence: 89%
“…Here we took a subsample of 88 individuals used in that study. After data assembly population assignment tests (see Supplementary methods) confirmed the existence of two spatially structured clusters (Oliveira et al, 2018) .…”
Section: Application With Uce Data -Testing Diversification Hypothesementioning
confidence: 92%
See 1 more Smart Citation
“…We also observed that the most common mtDNA haplotype is found all over the species distribution. Geomorphological barriers such as rivers (e.g., Kaefer, Tsuji‐Nishikido, Mota, Farias, & Lima, 2013; Oliveira, Martinez, et al, 2018; Pellegrino et al, 2005) and mountain ranges (e.g., Firkowski, Bornschein, Ribeiro, & Pie, 2016; Oliveira, Gehara, et al, 2018; Shepard & Burbrink, 2008) are usually responsible for patterns of geographic structure in taxa resulting from speciation events. Climatic oscillations or climatic gradients may also act at different latitudes, altitudes, and ecotone zones, directly affecting the genetic structure of some widely distributed species and species pairs (e.g., Boana albopunctata , Prado, Haddad, & Zamudio, 2012; Ameivula ocellifera , Oliveira et al, 2015; Polychrus acutirostris , Fonseca et al, 2018; Lygodactylus klugei , Lanna et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…2012a; Oliveira et al. 2018). Our partial Mantel test indicated that altitude resistance is not an important variable in explaining genetic diversity and structure within Colobosaura modesta ; rather, isolation‐by‐distance played a major role in the genetic structure of the species.…”
Section: Discussionmentioning
confidence: 99%